Help in hand after traumatic events: a randomized controlled trial in health care professionals on the efficacy, usability, and user satisfaction of a self-help app to reduce trauma-related symptoms. Issue 1 (31st December 2020) - van der Meer, Christianne A. I.; Bakker, Anne; van Zuiden, Mirjam; Lok, Anja; Olff, Miranda
ABSTRACT: Background : Despite the fact that many people are affected by trauma and suffer from posttraumatic stress symptoms (PTSS) there is a lack of easy-accessible interventions to self-manage these symptoms. Mobile apps may deliver low-intensity self-help to reduce trauma-related symptoms and empower individuals following trauma, such as high-risk professionals who are regularly exposed to potentially traumatic events. In this randomized controlled trial, we examined the efficacy, and evaluated the usability and user satisfaction of the app 'SUPPORT Coach' as a self-help tool to reduce trauma-related symptoms. Methods : Health care professionals (e.g. nurses, physicians, paramedics and ambulance drivers) completed an online screening on PTSS (T0). They were randomized when at least one PTSS was reported, either to the intervention (1 month unlimited access to SUPPORT Coach) or control condition (no access to SUPPORT Coach). Self-reported PTSS, negative trauma-related cognitions, psychological resilience, and social support were assessed online at baseline (T1), post-condition (T2), and 1 month follow-up (T3). Results : Of the 1175 participants screened, 287 (24.4%) indicated at least one posttraumatic stress symptom and were randomized. The majority of intervention condition participants (83%, n = 103) used SUPPORT Coach; they were slightly to moderately satisfied with the app. There was no significant group difference in change in PTSS and social support after one-month app usage. However, the intervention condition showed a greater decline in negative trauma-related cognitions at T2 and T3, and a larger increase in psychological resilience at T3 than the control condition. Conclusions : SUPPORT Coach without guidance could potentially provide easy-accessible self-help to diminish negative trauma-related cognitions, and strengthen resilience in coping with adversities. However, since the attrition rate was substantially higher in the intervention than in control condition, our findings should be interpreted with caution and warrant replication.